Resposta clínica, virológica e imunológica em pacientes HIV-1 submetidos a genotipagem pré terapia antirretroviral no estado de Goiás - Schmaltz, Cristhiane Dias Rodrigues (2011)
AIDS is responsible for over 2 million deaths each year, but the introduction of highly active antiretroviral therapy in 1996 has improved both the survival and the quality of life of patients. In Brazil, the Ministry of Health has been offering antiretroviral treatment free of charge for the last 15 years. However poor adhesion to treatment and extended use of antiretroviral drugs favor the selection and transmission of drug resistant viruses. This study assessed the clinical, virologic and immunologic responses of 97 patients genotyped before therapy between 2007-2008 by systematic revisions in the medical files for a medium period of 2 years. The pre-therapy genotypic tests identified 8/97 patients with transmitted resistance, 5/8 were men who have sex with men. According to WHO criteria similar clinical stage of the disease was observed in patients with and without resistant viruses. Among patients with wild virus 15/89 abandoned therapy, 4/89 were considered lost to follow up because they’ve been transferred to other clinics and 4/89 died, 3 due to AIDS causes, resulting in 66 patients followed up. Among 8 patients with transmitted resistance, one death not related to AIDS and 2 gave up therapy, resulting in 5 patients followed up. Upon therapy, patients with transmitted resistance presented an increase in the median of CD4+ cell counts of 215% whereas a 225% increase was observed in patients harboring wild virus. In both groups around 70% of patients had undetectable viremia following ARV treatment. The most common opportunistic infection was oral moniliasis. In conclusion, a wide variety of clinical outcomes was observed during short term follow up of patients genotyped pre-therapy. These outcomes ranged from therapeutic success represented by increase in CD4+ cell counts/undetectable viremia to death related or not to AIDS causes. A significant number of patients abandoned therapy. During follow up, there was no statistically significant difference in the clinical, virological and immunological outcomes of patients harboring wild or resistant virus. Altogether these results highlight the importance of pre-therapy genotypic tests for the adequate choice of ARV treatment preventing therapeutic failure and its immunological and clinical consequences, such as opportunistic infections and infections not related to AIDS. Moreover, the adequate prescription of ARV treatment avoids more complex drug regimens necessary for salvage therapy, which come at higher costs for the Brazilian public health system.